2018
DOI: 10.21037/jtd.2018.11.61
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen years of clinical experience with a modification of the Bentall button technique for total root replacement

Abstract: Background: We retrospectively reviewed our experience with the modified Bentall procedure and evaluated the short-and long-term results over a period of 18 years. Methods: Between 1999 and 2017, 89 patients with a mean age of 57.3±13.9 years underwent the modified Bentall operation with a slight modification for the correction of aortic root disease.Results: The operative mortality was 1.1% while the overall early mortality rate, defined as death within 30 days of initial hospitalization, was 2.2% (2/89). Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Nowadays, the "button" modification of the original Bentall procedure has been a standard operative technique and is the one most widely used for aortic root replacement as the safety and long-term efficacy have been confirmed. 14,15 In conclusion, an optimal treatment strategy should be based on a comprehensive assessment of the patient's condition. For aortic valve disease, whether to perform a single aortic valve replacement or with a simulta-neous aortic surgery for a prophylactic purpose should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the "button" modification of the original Bentall procedure has been a standard operative technique and is the one most widely used for aortic root replacement as the safety and long-term efficacy have been confirmed. 14,15 In conclusion, an optimal treatment strategy should be based on a comprehensive assessment of the patient's condition. For aortic valve disease, whether to perform a single aortic valve replacement or with a simulta-neous aortic surgery for a prophylactic purpose should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies of prosthetic aortic root replacements have reported a range of short-term mortality of 0.7% to 12% and long-term survival of 75% at 5 years to 91% at 16 years [Schachner 2005;Gelsomino 2003]. The wide range reported in these studies is partially explained by their inclusion of higher-risk patients such as urgent or emergency operations, dissections, endocarditis, redo sternotomies, previous AVR, specific genetic conditions, or older patients [Karangelis 2018]. When limited to elective operations only, mortality rates of the present study are comparable to other studies [Woldendorp 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Excision of a small cuff of surrounding aortic tissue as "coronary buttons" can considerably improve the visibility and facilitate the aortic-coronary anastomosis. Nowadays, the "button" modification of the original Bentall procedure has been a standard operative technique and is the one most widely used for aortic root replacement as the safety and long-term efficacy have been confirmed [Karangelis 2018;Westaby 2000].…”
Section: E796mentioning
confidence: 99%